1983
DOI: 10.1088/0022-3727/16/9/020
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pn coupling on open-circuit photovoltage decay in a silicon pn junction solar cell

Abstract: A theory of open-circuit photovoltage decay in a pn junction solar cell is presented which accounts for the pn coupling, i.e. the coupling between the diffused layer and the base of the solar cell. The results have been analysed in some detail which show how the voltage decay is influenced by the various parameters of the diffused layer. It is found that the decay is sensitive to pn coupling in the initial stages, particularly in those solar cells in which a heavy doping of the diffused layer may have caused s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

1986
1986
2008
2008

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
1
1
Order By: Relevance
“…To our knowledge this is the first study of the open-circuit voltage decay transient in DE Si and we demonstrated the possibility of exponential decay of V oc (t). However, the results in figure 2 are different from those observed in some dislocation-free solar cells with a linear decrease in V oc (t) after the illumination is switched off [21][22][23][24]:…”
Section: Open-circuit Voltage Decaycontrasting
confidence: 64%
See 1 more Smart Citation
“…To our knowledge this is the first study of the open-circuit voltage decay transient in DE Si and we demonstrated the possibility of exponential decay of V oc (t). However, the results in figure 2 are different from those observed in some dislocation-free solar cells with a linear decrease in V oc (t) after the illumination is switched off [21][22][23][24]:…”
Section: Open-circuit Voltage Decaycontrasting
confidence: 64%
“…It is found [11][12][13][14][15][16][17] that V oc can decay according to the exponential function. However, in some dislocation-free solar cells V oc is found [21][22][23][24] to decrease linearly with time after the illumination is switched off.…”
Section: Introductionmentioning
confidence: 99%